MEDIA LAYANAN INFORMASI KARIR SEKOLAH LANJUTAN BAGI SISWA (MELANKOLIS) UNTUK MENINGKATKAN PEMAHAMAN SISWA DALAM MEMILIH STUDI LANJUT SETELAH SMP - Acep Fitriana Zakaria (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2018)
This innovation work is based on an idea of the importance of quality improvement in guidance and counseling services. In this case, School Counselor is required to provide optimal service in providing career information services to students. Based on the findings at school, there are still many class IX students who have not been fully established in the process of selecting secondary schools after junior high school. Some of them explained that they were still confused, lacking understanding about the difference between high school and vocational high school, lack of knowledge about self potential, up to parents, because parents were seen as more entitled to the determination process, where they were financing the school process. The making of MELANKOLIS (Media for Career Education Services for High School Students) is seen as a form of facilitation for students in making an option to continue their studies after junior high school. The results of the use of media have been able to increase students' understanding of choosing secondary schools as evidenced by the acquisition of service evaluation results of 99, 56% categorized as Very Good. Where the level of satisfaction of students towards services shows that at 89, 28% of students rate Very Satisfying. In addition, MELANKOLIS has also been able to increase the enthusiasm of students in following services. These three results are an indicator of the successful implementation of MELANKOLIS in increasing students' understanding in choosing secondary schools after junior high school